Psychosocial functioning in pediatric patients with pectus excavatum and pectus carinatum - (:unkn) unknown (My University, 2017)
0

Background/aim: Pectus excavatum and pectus carinatum are the most commonly seen anterior chest wall deformities. Recent studies reveal that minimal invasive repair of pectus deformities improves the quality of life. Our aim is to assess the psychosocial functioning and sociodemographic characteristics of pediatric patients with pectus deformities and evaluate the differences between patients operated on with minimal invasive repair techniques and nonoperated patients. Materials and methods: Thirty-two patients with pectus deformities who were operated on 6 months or more before and 31 nonoperated patients participated in the study. The Children s Depression Inventory, Piers-Harris Children s Self-Concept Scale, Capa Social Phobia Scale for Children and Adolescents, Strengths and Difficulties Questionnaire - Self-Report Version (SDQ-SR), and State-Trait Anxiety Inventory for Children - Trait Version were completed by the patients. The SDQ-Parent Report Version (SDQ-PR) was completed by their parents. Results: There were no statistically significant differences between operated and nonoperated patient groups in terms of total scores on the psychiatric rating scales. Prosocial behavior subscale scores in SDQ-SR (P = 0.013) and SDQ-PR (P = 0.019) were lower in the operated group. Conclusion: Prosocial behavior levels were lower in the operated group. Further exploration of the psychosocial profile of pediatric patients with pectus deformities would better elucidate their needs in the course of their socioemotional development.
Keywords: Cerrahi